2019
DOI: 10.1371/journal.pone.0224222
|View full text |Cite|
|
Sign up to set email alerts
|

Double burden of maternal and child malnutrition and socioeconomic status in urban Sri Lanka

Abstract: Child malnutrition and maternal obesity are serious public health issues in Sri Lanka. This study explores the associations between socioeconomic status and the double burden of malnutrition among school-aged children and within their household. A total of 543 primary school children aged 5–10 years (204 boys and 339 girls) in Gampaha District, Sri Lanka, were included in the analysis. The nutritional statuses of thinness, normal, overweight, and obesity for children and mothers were defined according to WHO g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 17 publications
1
28
2
3
Order By: Relevance
“…A study done in the Colombo district shows a prevalence of obesity in boys was 4.3% and 3.1% in girls while our study indicated 8.7% in boys and 4.1% in girls [6]. The difference even years apart may be explained by the economic status of the populations.…”
Section: The Prevalence Of the Types Of Malnutrition In The Differentcontrasting
confidence: 57%
See 2 more Smart Citations
“…A study done in the Colombo district shows a prevalence of obesity in boys was 4.3% and 3.1% in girls while our study indicated 8.7% in boys and 4.1% in girls [6]. The difference even years apart may be explained by the economic status of the populations.…”
Section: The Prevalence Of the Types Of Malnutrition In The Differentcontrasting
confidence: 57%
“…Our study done in a single district in the North shows stunting in 10.9% of boys and 11.8% of girls. A similar study done in Colombo district showed stunting in 5.1% of boys and 5.2% of girls [6]. Low prevalence of stunting in two districts may be in uenced by the demography where both these districts are urban, and the economic status and educational level of the population is higher.…”
Section: The Prevalence Of the Types Of Malnutrition In The Differentmentioning
confidence: 72%
See 1 more Smart Citation
“…Students were selected from the index number of the attendance register using a random number table. Details of the sampling procedure have been described elsewhere [2]. In our analysis, we included 538 of 555 students who participated in the study, after excluding 17 students: 9 students whose age was not within the 5-10 years age group, and 8 students who had outlying or missing data for the main variables.…”
Section: Study Participantsmentioning
confidence: 99%
“…Child malnutrition is a serious public health concern worldwide [1]. In urban Sri Lanka, approximately one in three primary-school children suffer the double burden of malnutrition (thinness or overweight/obesity), defined by the World Health Organization (WHO) Child Growth Standards as body mass index (BMI)-for-age z-score (BAZ) that is <−2 standard deviation (SD) and >1 SD, respectively [2]. Stunting (low height-for-age) is also recognized as a critical indicator of chronic undernutrition in assessing child growth and development, and the proportion of stunting among children aged 5-6 years old is estimated at 8.7% in Sri Lanka [3].…”
Section: Introductionmentioning
confidence: 99%